Literature Study: Development Of Research Instruments For Educational Management Performance Evaluation - Aminah Chandra Kasih; Muhammad Muspawi (CV. ULIL ALBAB CORP, 2024)
This study aims to develop a research instrument for evaluating educational management performance, focusing on validity and reliability assessment. The study is a literature review that synthesizes findings from recent studies on educational management performance indicators. Using systematic literature analysis, the key variables affecting management performance were identified, including leadership quality, organizational culture, and resource allocation. This paper provides a detailed discussion on developing reliable evaluation tools. The results underline the importance of context-based adaptation of the instrument to suit various educational settings.